Acquired auditory-visual synesthesia: A window to early cross-modal sensory interactions - Pegah Afra; Michael Funke; Fumisuke Matsuo (Psychology Research and Behavior Management, 2009)
Pegah Afra, Michael Funke, Fumisuke MatsuoDepartment of Neurology, University of Utah, Salt Lake City, UT, USAAbstract: Synesthesia is experienced when sensory stimulation of one sensory modality elicits an involuntary sensation in another sensory modality. Auditory-visual synesthesia occurs when auditory stimuli elicit visual sensations. It has developmental, induced and acquired varieties. The acquired variety has been reported in association with deafferentation of the visual system as well as temporal lobe pathology with intact visual pathways. The induced variety has been reported in experimental and post-surgical blindfolding, as well as intake of hallucinogenic or psychedelics. Although in humans there is no known anatomical pathway connecting auditory areas to primary and/or early visual association areas, there is imaging and neurophysiologic evidence to the presence of early cross modal interactions between the auditory and visual sensory pathways. Synesthesia may be a window of opportunity to study these cross modal interactions. Here we review the existing literature in the acquired and induced auditory-visual synesthesias and discuss the possible neural mechanisms.Keywords: synesthesia, auditory-visual, cross modal